The Teacher’s Problems on Integrating Information and Communication Technology (ICT) in the English Language Teaching - Dwiono, Rija; Rochsantiningsih, Dewi; Suparno, S (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2018)
Technological innovation is rapidly changing which makes it hard to follow for the teacher. Thus, the practical application of ICT integration in teaching practices is necessary to be evaluated. This research aims to know the problems faced by the teacher on integrating ICT in teaching and how the teacher solves the problems. This case study focuses on the description of the individual teacher. The data were gained by employing observation and interview. It reveals that there are some problems occurred during the integration of ICT in teaching as well as describes the reasons why the problems could happen. One of them is that the teacher’s knowledge and ability to use pedagogical ICT in the classroom is still low. Lack of training to integrate ICT in teaching becomes a factor affecting the problem. This research can be a valuable reference for educational practitioners and the stakeholders as preparing the integration of ICT in teaching.